Aktualisasi Kesadaran Bela Negara Bagi Generasi Muda Dalam Meningkatkan Ketahanan Nasional - I Nengah Suriata (Public Inspiration : Jurnal Administrasi Publik, 2019)
The awareness of state defensive is the right and obligation for every citizen. In accordance with Article 27 Paragraph (3), Article 30 Paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Observing Article 27 Paragraph (3) and Article 30 Paragraph (1), implies that the state's defense effort in defending the state constitutes the rights and obligations of every citizen country with no exception the further regulation in the Law of the Republic of Indonesia Number 39 of 1999 concerning Human Rights, Republic of Law Number 3 of 2002 concerning National Defense, Law of the Republic of Indonesia number 34 of 2004 concerning TNI, Law of the Republic of Indonesia Number 20 of 2003 concerning the National Education System, and Law of the Republic of Indonesia number 12 of 2006 concerning Citizenship. Legal regulations cover the existence of state defense, but have not been able to realize awareness for the young generation. The number of violations of law carried out by the young generation including brawls, the participation of radical ideology (ISIS), drug abuse, and other illegal acts. The young generation was not actualize defending the country, so national security became less resilient which the country and nation collapsed. This research method used descriptive- qualitative analysis with observing a series of events that occur, observing the history of past observations based on current situations and conditions and using literature studies. The approach taken in the National Resilience perspective was multi-disciplinary or interdisciplinary. This approach also used to determine the extent of the state actualization of defense for young generation in national security. Next was the approach to find out that how much the role of the young generation in defending the country to strengthen national security. The population in this study was the young generation, while the sample was a purposive sample by searching on the internet for the involvement of young generation in violating the law. The conclusions of this study showed that the young generation experienced various violations of law, deviating from the basic values of the Pancasila, behaving radically and very disrespectfully, so that national resilience could not be strong. National Resilience is less resilient to Obstacles, Threat, Challenges and Disruptions (HTAG), which currently Indonesia is in implementing National Development.